Variability of some physical and chemical characters of the "cupuaçu" tree fruit - Fonseca, Carlos Eduardo Lazarini da; Escobar, José Ricardo; Bueno, Dalva Maria (Pesquisa Agropecuaria Brasileira, 2014)
Studies of variability, repeatability, and correlation were undertaken for serveral physical and chemical fruit characters from nineteen genotypes of "cupuaçuzeiro" (Theobroma grandiflorum) planted in Manaus, AM, Brazil. Repeatability estimates (R) have been found to be high for percentage of seed (R = 0.72) and percentage of pulp (R = 0.70). Phenotypic selection based on these characters may be effective. Correlations among all characters have shown that fruit weight is highly correlated with pulp weight (0.912), volume of the fruit (0.909), pell weight (0.901), and fruit length (0.752). All chemical characters have shown a poor correlation with all physical characters. Phenotypic selection based on pulp weight may increase indirectly the fruit weight. Selection for percentage of pulp will decrease indirectly the percentage of peel.